The Digital Upgrade of Opera Theatre: Intermedial Dramaturgies and Technological Visualities in Fanny & Alexander’s Spectacles - Pernice, Laura (Mimesis Journal, 2024)
Always bound to forms of intermedial dramaturgy, the company Fanny & Alexander (Luigi De Angelis and Chiara Lagani) since 2015 has started a new directorial path in the field of opera. By applying a methodological approach that catches the intermedial dimension of stagings according to the epistemological premises of digital performance and the lines research of Opera Studies, the article explores the question of their scenic and visual innovations through four specific case analyses: Il flauto magico (2015), Orfeo nel metrò (2019), L’isola disabitata (2021), Il ritorno di Ulisse in patria (2022).